Pain relief by paracervical block during manual vacuum aspiration for early miscarriage - Zerin, M. Ismat; Khatun, M. Sharifa; Tamanna, Zarin T.; Tamanna, Musammat R.; Amin, Rogina; Shilpi, Umme S.; Ara, Rifat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Early miscarriage is a common clinical problem that requires safe and effective management. Manual vacuum aspiration (MVA) under paracervical block is a minimally invasive procedure that helps to minimize pain during the procedure. This study aims to determine the safety and effectiveness of paracervical block in reducing pain during MVA for early miscarriage. Methods: A cross-sectional prospective observational study was conducted at the Department of Obstetrics and Gynaecology, Rajshahi Medical College Hospital, Bangladesh from January to June 2019. A total of 52 women with early miscarriages undergoing MVA were included. The procedure was done with a paracervical block given beforehand. Visual analog scale (VAS) was used to assess pain levels immediately after the procedure and 30 minutes later following the procedure. Results: The average age of the patients (57%) was 20-30 years. The mean gestational age was 6-10 weeks, and 65.4 percent of patients had incomplete abortion. Immediately after MVA, 69.23% of patients had mild pain severity (VAS 0 to 3), though this rose to 80.77% at 30 minutes post procedure. The mean VAS scores was 2.92±1.38 immediately after procedure and 2.57±1.44 after 30 minutes of the procedure. The procedure was considered acceptable by most patients (86.54%) with few adverse effects. Conclusions: During paracervical block for early miscarriage, MVA is a safe, effective and well tolerated means for pain relief and patient satisfaction.